Spatial inequality and policy implications of school physical education resource allocation: evidence from Shaanxi Province, China - Xu, Chengwei; Shi, Bing (Frontiers in Education, 2025)
IntroductionEquitable access to school physical education (PE) resources is central to education goals, yet sub-provincial spatial patterns in China remain underexamined.MethodsUsing 2024 data for 107 districts/counties in Shaanxi, we built a human–material–financial index with entropy weights, mapped distributions (GIS, standard deviational ellipse), tested clustering (Global/Local Moran’s I, LISA), decomposed inequality (Dagum’s Gini), and identified determinants and interactions (GeoDetector).ResultsResources follow a core–periphery gradient centered on central Shaanxi. Global Moran’s I = 0.105 (p = 0.037) indicates weak but significant clustering; LISA shows extensive Low–Low clusters. Overall inequality is modest (Gini = 0.176) but driven mainly by inter-city gaps (~48%) and cross-city overlap (~43%). Human resources dominate composite scores; key drivers are urbanization, PE funding share, student density, and teacher supply, with strong synergistic interactions.DiscussionFindings call for teacher-workforce strengthening, rebalancing investment toward facilities and professional development, and spatially targeted multi-lever policies—especially for persistent Low–Low clusters and urban–rural margins.